Impact of Working Capital on Corporate Performance: Evidence from India - Muruganandan, S.; Rakesh, T. S.; Dharani, M. (Finansy: teoriâ i praktika (Online), 2025)
The subject of this study is to empirically investigate the relationship between working capital and firm performance in India. The purpose of the study is to test the impact of optimal working capital on a firm’s market value and profitability. Methodology: The Generalised Method of Movement is employed to study the impact of working capital on a firm’s performance, measured as Return on Capital Employed and Enterprise Value to Sales. The results indicate a U-shape relationship between RoCE and the working capital component. On the contrary, the inventory turnover ratio has an inverted U-shape relationship with the market value of the firm. This study concludes that tight inventory management adds value at the initial stage, but strict inventory control erodes market value. The findings of the study support the optimum level of inventories to increase the firm’s performance, both in accounting terms and market value.